Modelling coastal planning in southwest Western Australia: complexity, collaboration and climate adaptation - Stocker, Laura; Kennedy, Deborah; Metcalf, S.; Dambacher, J.; Middle, Garry; Wood, David (Modelling and Simulation Society of Australia and New Zealand, 2011)
This action-research project investigates the extent to which current coastal planning arrangements can respond to climate change impacts such as coastal erosion and recession in the southwest of Western Australia. The complex social ecological system that comprises coastal planning in the region was modelled in a collaborative process. This took the form of a major action research workshop followed by further small workshops and interviews with key actors. The modelling process has implications for coastal planning as it shows that despite recent changes to coastal planning policy there are still significant areas of liability resulting from climate change that are not yet accounted for by governance. More generally, private and public coastal developments in WA are in a phase of rapid growth, with observable degradation of the coastal environment. Within the context of the model system, this implies that the positive feedback subsystems are strongly driving the system, and current levels of response to public liability and environmental advocacy are relatively weak and inadequate to achieve sustainable coastal management. For this system to be stable requires that negative system feedback be stronger than positive feedback. Future modelling efforts will investigate potential interventions and restructuring of governance system to achieve goals of sustainable development. Thus far, the main use of the model has been as a heuristic device to discuss the coastal planning system with key informants, and to identify constraints and opportunities to coastal adaptation through the planning system.